Antimicrobial action and clotting time of thin, hydrated poly(vinyl alcohol)/cellulose acetate films functionalized with LL37 for prospective wound‐healing applications. Issue 18 (21st October 2019) - Felgueiras, Helena P.; Teixeira, Marta A.; Tavares, Tânia D.; Homem, Natália C.; Zille, Andrea; Amorim, M. Teresa P.
ABSTRACT: Poly(vinyl alcohol)/cellulose acetate (PVA/CA) films were prepared via a new method that combines principles from solvent casting and phase inversion. To guarantee some degree of flexibility, films were produced with a higher percentage of PVA compared to CA, from 90/10 to 50/50. The antimicrobial peptide (AMP) LL37 was then anchored using dopamine as a binding agent. Films were characterized in terms of functional groups, thermal stability, tensile strength, porosity, swelling, and degradation (stability in physiological media at different pHs). The antimicrobial performance of LL37 surface‐modified films was tested against Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli in dynamic environment and in the presence and absence of an albumin interface. LL37 treated films demonstrated great antibacterial efficacy against the three kinds of bacteria, ≈75% inhibition for S. aureus, ≈85% for S. epidermidis, and ≈60% for E. coli, regardless of PVA/CA ratio. Presence of albumin reduced bacteria inhibition in all tested groups, most likely due to the binding of the protein molecules to the antimicrobial agents, reducing the free fraction available for bacterial killing. Films treated with LL37 accelerated clotting time (≈10 min) above vancomycin and bare surfaces, demonstrating great capacity to activate the intrinsic coagulation cascade. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48626. Abstract :